2D Square Octagonal Molybdenum Disulfide: An Effective Anode Material for LIB/SIB Applications. Issue 11 (4th October 2020) - Barik, Gayatree; Pal, Sourav
Abstract: The development of high‐performance energy storage devices is of great interest to both the scientific fraternity and has an appalling effect in day to day life. In this regard, square octagonal‐MoS2, a reported structural analog of MoS2, has become very interesting after the successful discovery of graphene. By using plane wave‐based density functional theory, 2D haeckelite structured so‐MoS2 is explored as an appealing anode for lithium‐ion batteries/Na‐ion batteries (LIBs/SIBs). The square MoS2 provides multiple numbers of Li/Na binding sites with high adsorption energies. The computed diffusion pathways and ion migration barriers on the surfaces of the so‐MoS2 probe that the diffusion process is ultrafast in nature. Moreover, at maximum Li/Na concentration, so‐MoS2 gives rise to an electrode that manifests a larger theoretical specific capacity of 670 mAh g −1 both for Li and Na storage, equivalent to that of h‐MoS2 . The lithiation/sodiation‐induced voltage range of the so‐MoS2 is quite feasible to be utilized as the anode, which is another vital factor influencing the performance of the LIBs/SIBs. All the above unique features unambiguously suggest that square octagonal MoS2 can become an efficient alternative anode material for rechargeable batteries. Abstract : Research into novel 2D materials has grabbed remarkable scientific consideration and has gained substantial momentum. In the context of this, square octagonal‐MoS2 is proved to possess exceptional mechanical properties and strong Li/Na adsorption energy with significantly lower Li/Na diffusion barrier energies along with admirable electronic conductivity. This makes so‐MoS2 an outstanding anode material for lithium‐ion batteries/Na‐ion batteries.